SWOT ANALYSIS FOR MARKETING STRATEGY OF TOURISM DESTINATION - Yanto Effendi; Sri Narti (Integrated Journal of Business and Economics (IJBE), 2020)
The purpose of this study was to determine  with SWOT  analysis for the marketing strategy of tourism destination  Mas Harun Bastari Lake, Mujerejo Village, Rejang Lebong Regency. SWOT analysis for as internal factor (Strengths,Weaknesses) and external factor (Opportunities, Threats).  IFAS value in Table 1 shows that the value of Strength is 14.30 and Weaknesses is 4.81, this shows that Strength is greater than Weaknesses with a total score of 19.11 with stable strength which can further strengthen to attract public interest in visiting the Lake Mas Harun Bastari is sustainable. the EFAS calculation of Mas Harun Bastari Lake in Mujerejo Village, Rejang Lebong Regency, the Opportunity value is 1.31 and Treats is 1.08, this shows that the calculation on the Opportunity value is greater than Threats with a total score of 2.39. In the SWOT diagram the values for Strength and Weaknesses are at 9.49 and the meeting point for Opportinity and Threats is at 0.23. This research shows that are in quadrant 1, which supports aggressive strategies. Marketing strategy of tourism destination  Mas Harun Bastari Lake, Mujerejo Village, Rejang Lebong Regency that can be done are renovating the lake area, adding facilities such as fishing locations and outbound equipment for visitors, placing security personnel in the lake area., giving permission to the community who will conduct activities on location, making agro tourism that can be enjoyed by visitors at the lake location, making a unique arrangement in the lake area, which differentiates it from other tourist attractions, providing comfort for visitors while in the lake area.  Key words : Marketing Strategy, Tourism Destination, SWOT